Are there modifiable risk factors affecting the prevalence of gallbladder polyps or those 5 mm or larger? A retrospective cross-sectional study. Issue 35 (3rd September 2021) - Kwon, Oh-Sung; Kim, Young-Kyu
Abstract : Abstract: Gallbladder polyps (GBPs), especially GBPs ≥5 mm in diameter, are clinically important because they can progress to gallbladder cancer. The known modifiable risk factors for GBP are obesity, metabolic syndrome, and dyslipidemia; however, there is limited evidence regarding specific modifiable risk factors for GBPs ≥5 mm in diameter. Therefore, this study is aimed to investigate the existence of modifiable risk factors affecting the prevalence of GBPs and GBPs ≥5 mm in diameter in a Korean population. A total of 10, 119 subjects who visited a single health-screening center at Jeju National University Hospital between January 2009 and December 2019 was included in this study. Binary logistic analyses were performed to identify risk factors affecting the prevalence of GBPs and GBPs ≥5 mm in diameter. The overall prevalence of GBPs and GBPs ≥5 mm in diameter were 9.0% and 4.1%, respectively. Multivariable analysis identified male gender as an independent risk factor affecting the prevalence of GBPs. Moreover, multivariable analysis revealed age and high-density lipoprotein cholesterol levels as independent risk factors for GBPs ≥5 mm in diameter. This study showed that gender was a risk factor affecting the prevalence of GBPs and that age and high-density lipoprotein-cholesterol levels were risk factors for the presence of GBPs ≥5 mm in diameter. High-density lipoprotein cholesterol levels could be a modifiable risk factor affecting the prevalence of large-diameter GBPs.